Production of Industrial Sugars from Petai Belalang - Rubena Malfia, Kamaldin; Dayang Salwani, Awang Adeni; Kopli, Bujang (i-CATS University College, 2024)
Leucaena leucocephala or locally known in Malaysia as ‘petai belalang’ was studied as an alternative material to produce sugar from cellulose. Analyses of the dried samples contain about 25% lignin, 50% cellulose and 17% hemicellulose. This dried sample was pulverised, mixed with water (10% w/v) and pre-treated by autoclaving. The resulting liquid and solid fractions were enzymatically hydrolysed and analysed for sugars, with a yield of 30% and 17%, respectively. Further analyses revealed that the sugars consisted mostly of glucose at 30% from the liquid and 40% from the solid fractions, clearly exhibiting higher content of glucose in the solid fraction. Accordingly, 1kg of fresh petai belalang biomass (84% dry matter) produces 395g of raw sugar, almost 50% of the total fresh weight. In a circular economy, this exhibits the potential of using waste biomass from petai belalang that can be utilised to produce raw sugar. Other sugars were traces of arabinose at 2% and cellulobiose at 1%. Purification of this raw sugar by filtration on PAC removed about 80% of the sugar, with a remaining amount of 87g (22%) purified glucose, at 55g and 32g from the liquid and solid portions.